Pengaruh Return on Investment, Debt to Asset Ratio, dan Interest Coverage Ratio terhadap Kinerja Keuangan pada Perusahaan Subsektor Keuangan di Indonesia Periode 2021-2024 - Fitri Febianti; Zulfa Khairina Batubara (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study addresses the inconsistency of financial performance indicators in Indonesia’s financial subsector during the post-pandemic recovery period. It aims to examine the effect of Return on Investment (ROI), Debt to Asset Ratio (DAR), and Interest Coverage Ratio (ICR) on financial performance proxied by Return on Equity (ROE). A quantitative approach was employed using secondary data derived from annual financial statements of financial subsector companies listed on the Indonesia Stock Exchange over the 2021–2024 period. The sample consisted of 10 companies selected through purposive sampling, resulting in 40 observations. Data were analyzed using multiple linear regression supported by classical assumption tests. The findings indicate that ROI and ICR have a positive and significant effect on ROE, while DAR does not show a significant effect. Simultaneously, ROI, DAR, and ICR significantly influence ROE. The model explains 44.5% of the variation in ROE, suggesting that other factors beyond the model also contribute to financial performance. These results highlight the importance of investment efficiency and the ability to meet interest obligations in improving profitability within the financial subsector.